2010
DOI: 10.1590/s1516-14392010000300013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage in water and thermocycling on hardness and roughness of resin materials for temporary restorations

Abstract: Purpose: This study evaluated the effect of storage in water and thermocycling on hardness and roughness of resin materials for temporary restorations. Material and Methods: Three acrylic resins (Dencor-De, Duralay-Du, and Vipi Cor-VC) were selected and one composite resin (Opallis-Op) was used as a parameter for comparison. The materials were prepared according to the manufacturers' instructions and were placed in stainless steel moulds (20 mm in diameter and 5 mm thick). Thirty samples of each resin were mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 33 publications
0
24
0
2
Order By: Relevance
“…Thus, the main effect of the water is to reduce interchain interactions such as entanglements and secondary bonding. This behavior creates more volume in the matrix and enhances the movement of the chain segments, thereby resulting in the decrease of the stiffness of the material 83) . A previous study 84) inferred that storage of composites in water and artificial saliva caused plasticization and degradation of the polymer matrix and degradation of the bond between the filler and coupling agent.…”
Section: Tcas In Dental Applicationmentioning
confidence: 99%
“…Thus, the main effect of the water is to reduce interchain interactions such as entanglements and secondary bonding. This behavior creates more volume in the matrix and enhances the movement of the chain segments, thereby resulting in the decrease of the stiffness of the material 83) . A previous study 84) inferred that storage of composites in water and artificial saliva caused plasticization and degradation of the polymer matrix and degradation of the bond between the filler and coupling agent.…”
Section: Tcas In Dental Applicationmentioning
confidence: 99%
“…In regard to time, it was verified that the surface roughness values increased after the thermocycling, possibly due to the formation of microfissures in the polymer matrix, incurred by thermal oscillations with detachments of load particles . According to Oliveira et al, thermal variations could generate tensions in the material, harming properties such as superficial roughness . In addition, the absorption of water promotes diverse chemical and physical processes, such as hydrolytic degradation of the polymer, also contributing to the increase of roughness .…”
Section: Discussionmentioning
confidence: 99%
“…However, this fact is not in agreement with the present study because there was a numerical increase of surface energy values after thermocycling. Oliveira et al suggest that resins with high amounts of small and regular pre‐polymeric particles are not, or minimally, influenced by thermocycling …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also degrades the matrix/filler interface directly by hydrolytic breakdown of the silane/filler interface and the surface of the filler particles, hence decreasing the mini flexural strength and surface micro-hardness of the three tested materials. Some authors (26,27) found a decrease in the flexural strength after thermocycling, others (28) reported that thermocycling decreased the surface micro-hardness of the composite resin materials. On the other hand, others (26) found an increase in the surface microhardness of indirect composite resin materials after thermocycling and claimed that findings to the 55°C of the thermocycling water path temperature which leads to further polymerization of the surface of the composite resins.…”
Section: Discussionmentioning
confidence: 99%